The effect of macroeconomics and social element toward personal bankruptcy in Malaysia - Choong, Mun Haw; Liew, Wei Ying; Loo, Jing Xuan; Ong, Cindy; Than, Yi Qian (2019)
Personal bankruptcy is one of the major issues that happened in Malaysia recently but the determinants of personal bankruptcy cases are still have the room for exploration. This research shows an empirical study of the macroeconomic factors and social elements leading to personal bankruptcy cases in Malaysia based on the available data from 1984 to 2017. The determinants in this research include lending rate, unemployment rate, and divorce cases. Autoregressive-Distributed Lag (ARDL) model was employed to study the relationship of lending rate, unemployment rate, and divorce cases toward personal bankruptcy cases. The results suggested that there is insignificant relationship between divorce cases and personal bankruptcy cases while lending rate and unemployment rate has significant relationship between personal bankruptcy cases. The results show that the rising of lending rate, unemployment rate and divorce cases will lead to the decrease of personal bankruptcy in Malaysia. Based on this study, future researchers are recommended to collect primary data to improve the accuracy of the results. Besides that, future researchers are also recommended to collect data not only based on the macroeconomic disaggregate level but also based on the disaggregate level of individual family. Lastly, it is advisable to lengthen the study period of research so that future researchers could be more focused in studying more relevant topics.